2011
DOI: 10.1053/j.seminoncol.2011.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of MicroRNAs Contribute to Colon Carcinogenesis

Abstract: MicroRNAs are being evaluated as biomarkers and therapeutic targets for colon cancer. MicroRNAs have a functional role in the initiation and progression of colon cancer. Altered microRNA expression is found in tumors and their expression patterns may serve as useful cancer biomarkers. Polymorphisms in microRNAs or microRNA binding sites may modify ones risk of developing cancer. As we continue to improve our understanding of the role for microRNAs in the initiation and progression of cancer, one goal is to gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 73 publications
2
57
1
Order By: Relevance
“…microRNAs, a newly discovered class of non-coding small RNAs, have been recognized as potential targets for tumor treatment due to their important roles in carcinogenesis and cancer progression via binding to specific complementary sites within the 3' untranslated regions (3'UTR) of their target gene mRNAs (16)(17)(18). Accumulated studies have shown that miRNAs may function as oncogenes or tumor suppressors in the tumorigenesis of various human cancers depending on the cellular contexts and the target genes that they regulate.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs, a newly discovered class of non-coding small RNAs, have been recognized as potential targets for tumor treatment due to their important roles in carcinogenesis and cancer progression via binding to specific complementary sites within the 3' untranslated regions (3'UTR) of their target gene mRNAs (16)(17)(18). Accumulated studies have shown that miRNAs may function as oncogenes or tumor suppressors in the tumorigenesis of various human cancers depending on the cellular contexts and the target genes that they regulate.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence shows that miRNAs are involved in the biological processes related to apoptosis, proliferation, differentiation, invasion and metastasis, while its deregulation is crucial to cancer initiation and progression. [16][17][18][19] In an initial screen for miRNAs differentially expressed in human breast cancer cells, the three most significantly upregulated miRNAs, miR-155, miR-9 and microRNA-10b (miR-10b), were identified. 20 MiR-10b is a particularly interesting candidate given its close correlation with metastatic behaviors.…”
mentioning
confidence: 99%
“…Thus, variations in these sequences may result in significant functional consequences, making them ideal candidates for cancer risk prediction. Many have been validated as potential oncogenes or tumor suppressor genes in CRC, such as miR-143, miR-145, miR-21, and miR200c (Schetter and Harris, 2011). miRNA expression profile analyses indicate that these sequences play an etiological role in the initiation and progression of this condition.…”
Section: Differentially Expressed Mirnas In Crcmentioning
confidence: 99%